Presentation - Víctor R. Martín Fiorino (Telos: Revista de Estudios Interdisciplinarios en Ciencias Sociales, 2003)
This issue of TELOS opens a space for academic debate on the ideas and practices current in today’s society, considered from convergent perspectives that respond to historical, educational, ethical, cultural, legal and organizational searches and research. They show that current thought looks at human beings primarily from their future: it asks about the very possibility of this future and its characteristics, radically expressed by two questions formulated at the end of the 20th century; Can man survive? Can we live together?